Complementary Roles for Fibrin(ogen), Thrombospondin and vWF in Mediating Shear-dependent Aggregation of Platelets Stimulated at Threshold Thrombin Concentrations - Kasirer-Friede, Ana; Legrand, Chantal; Frojmovic, Mony M. (Thrombosis and Haemostasis, 2001)
We have evaluated the relative contribution of the adhesive ligands, von Willebrand factor (vWF), fibrinogen (Fg) and thrombospondin (TSP), all surface-expressed on washed platelets (WP) activated with a threshold thrombin concentration (~ 0.04 U/ml), to platelet micro-aggregation (PA) at shear rates (G) from 300-2000 s-1. In suspensions of thrombin-activated WP sheared immediately (τ0), all three ligands were required for optimal aggregation at all G, as shown by a 50-70% inhibition of capture efficiencies of PA (measured from initial rates of PA), by antibodies (Abs) directed against each protein. This aggregation involved both GPIb and GPIIbIIIa, as indicated by ~ 80% and 100% inhibition by Ab 6D1 and Ab 10E5, respectively. For WP preexposed to thrombin for 10 min to ensure maximal surface expression of secreted ligands and activated GPIIbIIIa (τ10), vWF was predominantly required at all G (63-75% inhibition by anti-vWF Ab), together with TSP (35-50% inhibition by anti-TSP Ab). Under these conditions, Fg was extensively converted to fibrin, so that fibrin, rather than Fg, could participate in microaggregation, with GPIb less required than GPIIbIIIa as indicated by a 30-60% inhibition by Ab 6D1 as compared to 100% inhibition by Ab 10E5. Our results show that interactions between multiple ligands and receptors favour microaggregation depending on shear and thrombin activation conditions.
Keywords: vWF; fibin(ogen); thrombospondin